Klasifikasi Jenis Kelamin menggunakan Pitch Suara dengan metode Pitch Detection Algorithm - Irham Surya Pratama; Felix Indra Kurniadi (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2018)
Abstract—Gender classification is one of the major problems in speech analysis. Human voices exhibit very interesting aspects i.e. pitch, median, frequency etc. In this research we proposed an approach using pitch to classify each gender. Pitch Detection Algorithm were used as main method. This method gives 61% using Pitch Detection Algorithm